2019
DOI: 10.1186/s40463-019-0391-2
|View full text |Cite
|
Sign up to set email alerts
|

Overnight oximetry in children undergoing adenotonsillectomy: a single center experience

Abstract: BackgroundObstructive sleep apnea (OSA) is the most common indication for adenotonsillectomy in children. Home-based sleep oximetry continues to be used in the diagnosis of pediatric OSA despite a lack of correlation with lab-based polysomnography. This study investigates whether factors influence surgeons in selecting patients for home-based sleep oximetry, how the study findings are used in patient management, and whether abnormal oximetry findings are associated with post-operative complications.MethodsA re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The mean age of our patients was 7 years, which is slightly higher than in some studies, though identical to that of other published series, such as the Childhood Adenotonsillectomy Trial (CHAT) [ 15 , 39 , 40 ]. In our opinion this was not due to selection bias, as all patients were analysed systematically, without exclusion, as part of a real-life study.…”
Section: Discussionsupporting
confidence: 87%
“…The mean age of our patients was 7 years, which is slightly higher than in some studies, though identical to that of other published series, such as the Childhood Adenotonsillectomy Trial (CHAT) [ 15 , 39 , 40 ]. In our opinion this was not due to selection bias, as all patients were analysed systematically, without exclusion, as part of a real-life study.…”
Section: Discussionsupporting
confidence: 87%
“…Modifying the algorithm with information from PSG or home sleep testing rather than oximetry alone may further improve the algorithms predictive capacity. Follow-up studies may explore long-term outcomes and comparing post-operative complications [21] for patients who were triaged based on the algorithm versus a control group.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, professional associations such as the American Academy of Pediatrics, American Academy of Sleep Medicine, American Academy of Otolaryngology-Head and Neck Surgery Foundation, European Respiratory Society, have further suggested that in the presence of characteristic OSA symptoms and some supportive physical findings, implementation of simplified testing procedures could replace the gold standard PSG in the form of home-based multichannel respiratory recordings or even single channel overnight oximetry. 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 We have been among the latter, particularly based on the concern of limited access to PSG testing for children along with excessive financial costs. Development of such validated scalable diagnostic tools that can be automated would substantially reduce financial burden as well as time consuming labor involved in scoring and interpretation of polysomnograms.…”
Section: What Constitutes Mild Obstructive Sleep Apnea (Osa)?mentioning
confidence: 99%
“…Development of such validated scalable diagnostic tools that can be automated would substantially reduce financial burden as well as time consuming labor involved in scoring and interpretation of polysomnograms. 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 Such approaches if adopted more universally, would result not only in expedited evaluation of many children who currently are required to wait for long periods of time before being diagnosed, but would also facilitate access to pediatric sleep laboratories for those children in whom the diagnosis is uncertain, or the clinical presentation is more complex and requires more sophisticated diagnostic approaches.…”
Section: What Constitutes Mild Obstructive Sleep Apnea (Osa)?mentioning
confidence: 99%
See 1 more Smart Citation